Pendampingan Pembelajaran Qira’at dan Ilmu Al-Quran di Komplek Tahfiz Sukan Sofiuddin Selangor, Malaysia - Putra, Ali Musri Semjan; Jamal, Khairunnas; S, Mochammad Novendri; Syafii (Jurnal Pengabdian Kepada Masyarakat, 2025)
The community service activity titled "Assistance in Qira’at and Qur’anic Studies Learning at Komplek Tahfiz Sukan Sofiuddin, Selangor, Malaysia" aimed to improve the quality of Qira’at and Qur’anic studies through a participatory approach. This program targeted enhancing the competencies of educators, increasing student motivation, and utilizing interactive digital media. Conducted over two days, the activity was attended by five teachers and 84 students from various halaqahs and age levels. The results demonstrated significant impacts on improving teachers’ abilities to effectively teach Qira’at variations and create an engaging classroom environment. Students exhibited greater interest in the technical aspects of Qira’at, with significantly improved learning outcomes. Moreover, the direct assistance achieved success in terms of quantity, with participant numbers exceeding the initial target. Despite challenges such as limited student understanding, varying technological skills among participants, and the short duration of training, implemented solutions effectively addressed these issues. This program has great potential to be replicated in other tahfiz institutions, supported by participatory approaches and digital technology. Therefore, this activity made a tangible contribution to the innovative and sustainable development of Qur'anic education.